HIV-1 drug resistance-associated mutations in relation to viral load among HIV/AIDS patients at Dr. M. Djamil-Hospital Padang - Nadia, Rizka; Elvira, Dwitya; Raveinal, Raveinal (Universa Medicina, 2024)
BackgroundAccording to the WHO, 38 million people suffer from HIV worldwide and according to the HIV Drug Resistance Report, the prevalence of antiretroviral therapy (ART) resistance is 3-29%. Drug resistance-associated mutations (DRAMs) are the presence of one or more HIV mutations that reduce the ability of certain drugs to inhibit viral replication and that will increase viral replication and HIV RNA, which can lead to therapeutic failure. The objective of this study was to determine the prevalence of HIV-1 DRAMs among patients with chronic HIV-1 infections and to compare HIV RNA viral load between M184V and K103N mutations. Methods A cross-sectional was conducted involving 80 patients with HIV who met the inclusion criteria. The study subjects were examined for genotype and HIV RNA viral load, both using the polymerase chain reaction (PCR). Data were analyzed with the Kruskal-Wallis test. Results The overall drug resistance mutation prevalence was 10.0%. The most common mutations were M184V and K103N. There was a significant difference between the median HIV RNA viral load counts in patients with either M184V or K103N, and with both M184V and K103N mutations, the values being 45.420, 13.207, and 97.517 copies/mL, respectively (p<0.001). Conclusion The HIV RNA viral load count was higher in the mutation group than in the group without mutation. Long-term and ongoing surveillance of HIV DRAMs among these patients is necessary, which will help us to adjust the treatment regimen.